State educational agencies in an uncertain environment: Understanding state provided networks of English Language Arts curricular resources - Serena J. Salloum; Emily M. Hodge; Susanna L. Benko (Arizona State University, 2020)
Rapid adoption of the Common Core State Standards (CCSS), the Race to the Top (RTTT) competition, and backlash around these policies created widespread uncertainty among state educational agencies (SEAs). SEAs may have not had a clear direction about how to support standards implementation in a new context, and therefore, may have looked to their professional networks, their geographic neighbors or other highly regarded SEAs, or other sources for information and resources to guide their decisions about where to send teachers for information about standards. Drawing on institutional theory (Meyer Rowan, 1977) and isomorphism specifically (DiMaggio Powell, 1983), we posit that coercive forces (primarily due to RTTT application and CCSS status) as compared to mimetic and normative forces influenced the organizations to which SEAs turn for curriculum materials. Using Multiple Regression Quadratic Assignment Procedure and a data set of over 2,000 state-provided resources for secondary English Language Arts teachers from all 50 states and Washington, D.C., we indeed found that coercive forces had a relationship with shared organizational ties, demonstrating that RTTT application and CCSS adoption influenced resource provision.